2022
DOI: 10.1088/1361-6560/ac71f0
|View full text |Cite
|
Sign up to set email alerts
|

Iterative metal artifact reduction on a clinical photon counting system—technical possibilities and reconstruction selection for optimal results dependent on the metal scenario

Abstract: To give an overview about technical possibilities for metal artifact reduction of the first clinical photon-counting CT system and assess optimal reconstruction settings in a phantom study, assessing monoenergetic imaging (VMI) and iterative metal artifact reduction (iMAR). Scans were performed with 120 kV and Sn140 kV on the first clinical photon-counting detector CT scanner. To quantify artifact reduction, anthropomorphic phantoms (hip, dental, spine, neuro) were assessed, in addition to a tissue characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 39 publications
8
23
1
Order By: Relevance
“…This might have been one reason for the weaker artifact suppression by high keV VMIs than has previously been described and would concur with Zhu et al 5 who reported that higher keV VMIs especially reduced artifacts caused by small dental fillings. Anhaus et al 17 even tested multiple materials in their phantom study on a PCD-CT scanner and found no benefit by high-energy VMI on metal with high atomic number as used for dental restauration. Kernel choice does not influence average CT values in ROIs of the size used in our analysis; yet, it affects image noise, resulting in higher AIXs for sharper reconstruction kernels, a trivial consequence of the higher spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This might have been one reason for the weaker artifact suppression by high keV VMIs than has previously been described and would concur with Zhu et al 5 who reported that higher keV VMIs especially reduced artifacts caused by small dental fillings. Anhaus et al 17 even tested multiple materials in their phantom study on a PCD-CT scanner and found no benefit by high-energy VMI on metal with high atomic number as used for dental restauration. Kernel choice does not influence average CT values in ROIs of the size used in our analysis; yet, it affects image noise, resulting in higher AIXs for sharper reconstruction kernels, a trivial consequence of the higher spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
“…This might have been one reason for the weaker artifact suppression by high keV VMIs than has previously been described and would concur with Zhu et al 5 who reported that higher keV VMIs especially reduced artifacts caused by small dental fillings. Anhaus et al 17 even tested multiple materials in their phantom study on a PCD-CT scanner and found no benefit by high-energy VMI on metal with high atomic number as used for dental restauration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of those threshold images includes only X‐ray photons with an energy exceeding a predefined energy threshold 33,34 . As it is implemented in conventional iterative MAR in the routine of the clinical PCD‐CT system, the described method was applied on both threshold images of the PCD scan separately, and the monoenergetic images are then generated from both threshold images 35 . The PCD images are shown at an energy level of 65 keV as the standard energy level for a 120 kV scan.…”
Section: Methodsmentioning
confidence: 99%
“…Anhaus et al. recently showed that iterative metal artifact reduction (iMAR) could be combined with VMIs with a clinical PCD‐CT scanner to obtain better MAR 48 . It is possible that similar results could be obtained by first applying TRMAR to obtain a reduced artifact image, and then an additional method could be applied to further improve the results.…”
Section: Discussionmentioning
confidence: 99%